COVID-19 Pandemic Impact on Academic Global Health Programs: Results of a Large International Survey. Issue 1 (29th September 2022) - Rose, Elizabeth S.; Rabin, Tracy L.; Samaan, Jenny; Hudspeth, James C.; Ibrahim, Layan; Azain, Maria Catalina Padilla; Evert, Jessica; Eichbaum, Quentin
Background: The COVID-19 pandemic caused significant disruptions in international communications and travel for academic global health programs (AGHPs) in both high-income countries (HICs) and low- and middle-income countries (LMICs). Given the importance of international travel and communication to AGHPs, the pandemic has likely had considerable impact on the education, research, and administrative components of these programs. To date, no substantive study has determined the impacts of the COVID-19 pandemic on AGHPs in HICs and LMICs. This study assessed the impacts and resultant adaptations of AGHPs to pandemic realities with the goal of sharing strategies and approaches. Methods: This study applied a mixed methods sequential explanatory design to survey AGHPs in HICs and LMICs about the impacts of the COVID-19 pandemic on three program domains: education, research, and administration. First, we surveyed a range of AGHP stakeholders to capture quantitative data on the pandemic's impact. Subsequently we conducted semi-structured interviews with select survey participants to gather qualitative data expanding on specific survey responses. Data from both phases were then compared and interpreted together to develop conclusions and suggest adaptive/innovative approaches for AGHPs. Results: AGHPs in both HICs and LMICs were significantly impacted by the pandemic in all three domains, though in different ways. While education initiatives managed to adapt by pivoting towards virtual learning, research programs were impacted more negatively by the disruptions in communication and international travel. The impact of the pandemic on scholarly output as well as on funding for education and research was quite variable, although LMIC programs were more negatively impacted. Administratively, AGHPs implemented a range of safety and risk mitigation strategies and showed a low risk tolerance for international travel. The pandemic posed many challenges but also revealed opportunities for AGHPs. Conclusions: The COVID-19 pandemic disrupted AGHPs in HICs and LMICs in expected and unexpected ways. Programs noted some unanticipated reductions in education program funding, negative impacts on research programs, and reduced scholarly output. Many programs reported well-coordinated adaptive responses to the pandemic including, for instance, virtual (in place of in-person) collaboration in research. The pandemic will likely have lasting impacts with regard to education, research collaborations, and administration of programs.